Health literacy and healthcare service utilisation in the 12-months prior to entry into residential alcohol and other drug treatment. (January 2022) - Degan, Tayla J.; Kelly, Peter J.; Robinson, Laura D.; Deane, Frank P.; Baker, Amanda L.
Highlights: People living with substance use disorders access high rates of healthcare services. Three health literacy profiles were identified; low, moderate, and high health literacy. No differences between health literacy profiles and primary or acute healthcare use. Abstract: Introduction: Health literacy refers to an individual's capacity to gather, process and understand health information, make appropriate health decisions, and engage adequately with healthcare services. Inadequate health literacy has been linked to an increase in acute healthcare utilisation. Research suggests that people living with substance use disorders also access acute healthcare services at high rates. The study investigates whether overall health literacy is related to this population's use of general healthcare services. Methods: A total of 568 participants were recruited from residential substance use treatment services located in NSW, Australia, as part of a randomised controlled trial; the Continuing Care Project. All participants completed a face-to face baseline questionnaire, which included the Health Literacy Questionnaire; a measure of multidimensional health literacy. Latent profile analysis was used to examine health literacy profiles, with multinominal regression analysis examining if healthcare service utilisation was related to these profiles. Results: Three profiles of health literacy were identified and termed lowest ( n  = 86, 15.1%), moderate ( n  = 338, 59.5%) and highest health literacy ( n  = 144, 25.4%). The sample accessed both primary and acute healthcare services at high rates. When controlling for demographic variables, there were no significant differences identified between health literacy profiles and service use. Discussion/Conclusions: This study was the first to use a multidimensional health literacy tool to examine health literacy and general healthcare service utilisation for people attending residential substance use disorder treatment. This population access high levels of healthcare services, however the role that health literacy may play in helping reduce acute healthcare use requires further investigation.